Targeting Metabolism to Improve the Tumor Microenvironment for Cancer Immunotherapy - Bader, Jackie E; Voss, Kelsey; Rathmell, Jeffrey C (Molecular cell, 2020)
The growing field of immune metabolism has revealed promising indications for metabolic targets to modulate anti-cancer immunity. Combination therapies involving metabolic inhibitors with immune checkpoint blockade (ICB), chemotherapy, radiation, and/or diet now offer new approaches for cancer therapy. However, it remains uncertain how to best utilize these strategies in the context of the complex tumor microenvironment (TME). Oncogene-driven changes in tumor cell metabolism can impact the TME to limit immune responses and present barriers to cancer therapy. These changes also reveal opportunities to reshape the TME by targeting metabolic pathways to favor immunity. Here we explore current strategies that shift immune cell metabolism to pro-inflammatory states in the TME and highlight a need to better replicate physiologic conditions to select targets, clarify mechanisms, and optimize metabolic inhibitors. Unifying our understanding of these pathways and interactions within the heterogenous TME will be instrumental to advance this promising field and enhance immunotherapy.